Spread of virus during soccer matches - Knudsen, N. S.; Demetry Thomasen, M. M.; Bull Andersen, T. (MedRXiv, 2020)
In the present study, the exposure to virus during soccer matches is calculated. Tracking data from 14 elite matches was used. One player in each match was carrying a virus. The exposure score (measured in seconds) was calculated as time spent closer than 1.5m from the infected player or time spent in an exponentially declining zone where the infected player was positioned earlier. The results reveal that, on average, each player was exposed for 87.8s per match.